Synthesis, characterization, and antibacterial activity of thymol loaded SBA-15 mesoporous silica nanoparticles. Issue 6 (3rd June 2019) - Shahriarinour, Mahdi; Divsar, Faten; Eskandari, Zohre
Abstract: In the present study, SBA-15 mesoporous nanoparticles were synthesized by hydrothermal method and functionalized with amino group by post grafting method (SBA-15-NH2 ), then thymol was loaded into SBA-15-NH2 (SBA-15-NH2 @ thymol). The SBA-15-NH2 mesoporous silica and SBA-15-NH2 @ thymol nanoparticles were analyzed by powder X-ray diffraction (PXRD), Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), UV-Vis diffused reflectance (DRS), Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) techniques. The antibacterial effect of thymol and SBA-15-NH2 @thymol nanoparticles were investigated against pathogenic bacteria of S. aureus and E. coli . The zone of inhibition thymol and SBA-15-NH2 @thymol were 26 mm and 14 mm against S. aureus . The zone of inhibition against E. coli was lower than that of S. aureus . The most of antibacterial effect of thymol was seen at concentration of 40 mg/ml against S. aureus . Thymol and SBA-15-NH2 @thymol show antibacterial activity against gram-positive and gram-negative pathogenic bacteria.